Translation and Validation of Pediatric Functional Independence Measure Scale in Urdu Language among Preterm Children - Qurat-Ul-Ain Sherazi, Shoaib Waqas, Muhammad Tariq, Hafiz Muhammad Asim, Asifa Javaid, Imran Ghafoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To translate and validate the Pediatric Functional Independence Measure (WeeFIM) scale in Urdu language among preterm children for the purpose of cross cultural adaptation. Methods: The validation study was carried out at Lahore College of Physical Therapy (LMDC). In Lahore, the existent English version of the WeeFIM scale, already validated as an excellent tool for measuring functional limitations in the pediatric population, was forward and backward translated into the Urdu language to test its validity and cross-cultural adaptation as per Bombardier, Beaton, and Guillemin’s guidelines. Forward and backward translation was conducted by two independent translators with adequate credentials; one of the translators was a professor of Urdu literature and the other was a medical professional working in the field. A final Urdu version of the WeeFIM scale was created and discrepancies were resolved by bilingual experts, which were then validated by an expert panel of 10 therapists. The validated version was then tested on a sample size of 52 children with a history of preterm birth in next phase to determine the reliability of Urdu version of instrument. Results: The Cronbach’s alpha for the Urdu version of WeeFIM was calculated to be 0.965 after translation, while Cronbach’s alpha after application to preterm children was 0.837. The inter-item correlation after application to the concerned population was calculated to be 0.636, 0.523, and 0.754 for all three domains, respectively. Conclusion: Urdu version of WeeFIM scale is valid and reliable tool for preterm children. Keywords: Translation, Validation, Preterm children, WeeFIM-I, WeeFIM-II.